2015
DOI: 10.1016/j.prosdent.2015.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Single-stage osseointegrated implants for nasal prosthodontic rehabilitation: A clinical report

Abstract: Malignant tumors in the nasal region may be treated by means of invasive surgical procedures, with large facial losses. Nasal prostheses, retained by osseointegrated facial implants, instead of plastic surgery, will, in most patients, offer good biomechanical and cosmetic results. This clinical report describes the prosthetic rehabilitation of a patient with nasal cancer who had the entire nasal vestibule removed in a single-stage surgical procedure in order to shorten the rehabilitation time. The nasal prosth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Taking the anatomical and reconstructive needs of the patient into account, it is the opinion of the authors that success rates are generally good for facial reconstruction and that most implants are able to retain their associated prosthesis and that such implants are a viable alternative to autogenous reconstruction. In addition, rehabilitation with single-stage osseointegrated implants and prostheses using intrinsic pigmentation may be able to offer fast treatment time and esthetic confidence 54…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Taking the anatomical and reconstructive needs of the patient into account, it is the opinion of the authors that success rates are generally good for facial reconstruction and that most implants are able to retain their associated prosthesis and that such implants are a viable alternative to autogenous reconstruction. In addition, rehabilitation with single-stage osseointegrated implants and prostheses using intrinsic pigmentation may be able to offer fast treatment time and esthetic confidence 54…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Tjellström et al redesigned intraoral endosseous implants and was the first to use them extraorally to retain bone‐anchored hearing aids. Since then, osseointegrated endosseous implants have been used to retain facial prostheses . Studies have shown that patient satisfaction and quality of life with implant‐retained facial prostheses is significantly better than adhesive‐retained prostheses .…”
Section: Introductionmentioning
confidence: 99%
“…Maxillofacial prosthodontic treatment protocols for adult rehabilitation are well documented in the prosthodontic literature, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] especially noted in a systemic review of classification of maxillectomy defects by Bidra et al 15 Replacement of facial tissues and organs with prosthodontic materials, including the use of osseointegrated implants for improved retention, has provided patients afflicted with surgical and traumatic loss with rehabilitation permitting them to return to reasonable function and social acceptance.…”
mentioning
confidence: 99%